2016
DOI: 10.14245/kjs.2016.13.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Ossification of Posterior Longitudinal Ligament and Increased Bone Mineral Density in Patients with Ossification of Nuchal Ligament

Abstract: ObjectiveThere are also few studies demonstrating the relationship between ossification of nuchal ligament (ONL) and ossification of posterior longitudinal ligament (OPLL). We compared the prevalence, location, and type of OPLL between patients with ONL and matched patients without ONL.We also compared the bone mineral densities (BMDs) between the 2 groups.Methodstotal of 124 cervical ONL patients were enrolled in this study. The control group of 124 patients was matched with 124 patients with ONL by age and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A total of 16 studies were subsequently assessed by full‐text review, and 6 studies were excluded for the following reasons: no full text ( n = 2), duplicate data ( n = 1), and not reporting the association between ONL and OPLL ( n = 3). Finally, the remaining 10 studies 23, 25–27, 31–36 met our selection criteria and were included in the review. The detailed search strategy through the PRISMA flow diagram is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 16 studies were subsequently assessed by full‐text review, and 6 studies were excluded for the following reasons: no full text ( n = 2), duplicate data ( n = 1), and not reporting the association between ONL and OPLL ( n = 3). Finally, the remaining 10 studies 23, 25–27, 31–36 met our selection criteria and were included in the review. The detailed search strategy through the PRISMA flow diagram is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical OPLL was diagnosed with cervical CT. As for the extent of COPLL, the common assessment criteria were applied in 2 studies: there was a short‐level (1–3 levels) OPLL group and a long‐level (4–6 levels) OPLL group based on the number of intervertebral spaces involved by OPLL 23, 26 . Long‐level OPLL was considered more severe than short‐level OPLL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Most recent studies have used CT or MRI for diagnosis. 9-12 However, OPLL of cervical spine diagnosis using lateral X-rays can lead to underestimation of the condition, whereas MRI is prone to overestimation. This is because of the difficulty in distinguishing between hypertrophy and ossification.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that investigated multiple types of ossification of the ligaments, including OPLL, ossification of ligamentum flavum, ossification of anterior longitudinal ligament, DISH, and ossification of nuchal ligament, reported that there were more patients with multiple combined types of ossification than there were those with only one type [ 1 ]. Additionally, both patients with one type and those with multiple types of ossification had significantly greater bone mineral density (BMD) than did those with no ossification [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%